2013
DOI: 10.2486/indhealth.ms1325
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Exposure to Airborne Endotoxin: A Review of the Literature on Sampling and Analysis Methods

Abstract: Assessment of exposure to airborne endotoxins has been studied for several years, especially in occupational environments, but a large number of procedures are used for sampling and analysis. This lack of standardization makes it very difficult to compare results and set internationally accepted threshold limit values (TLVs) or occupational exposure limits (OELs) for endotoxin exposure. This paper reviews the methods reported, using advanced bibliographical search techniques: 82 papers published from 2004 to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 83 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…These dusts are present at many industrial and agricultural workplaces as well as in homes 1, 2 . A constituent of virtually all organic dusts are Gram-negative bacteria (GNB) endotoxins 1, 3, 4 . Endotoxins are highly abundant integral membrane glycolipids present uniquely in the outer membrane (OM) of GNB, in shed OM-rich nanoparticles (OM blebs) from these bacteria, and as supramolecular aggregates after extraction and purification of endotoxin from the GNB OM 57 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These dusts are present at many industrial and agricultural workplaces as well as in homes 1, 2 . A constituent of virtually all organic dusts are Gram-negative bacteria (GNB) endotoxins 1, 3, 4 . Endotoxins are highly abundant integral membrane glycolipids present uniquely in the outer membrane (OM) of GNB, in shed OM-rich nanoparticles (OM blebs) from these bacteria, and as supramolecular aggregates after extraction and purification of endotoxin from the GNB OM 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Many GNB endotoxins are remarkably potent stimuli of human and murine inflammatory and immune responses 5, 11 . The ability of inhaled or aspirated purified endotoxin to simulate many of the effects of inhaled organic dusts on airway immunity and pathophysiology 3, 4, 12, 13 has stimulated extensive efforts to measure endotoxin contamination of diverse organic dusts and test experimental mitigation strategies directed at blocking or modulating endotoxin-triggered innate immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…First, the finest fraction is the most relevant both to the mass and, of course, particle numbers during our sampling activities, and the ratio between PM 3 and PM 3-10 is at least 4 with an average, for all sampling, equal to 8. Second, other previous studies have shown the possible association of the endotoxin with the finest fraction with respect to the coarse, with particular regard to indoor and semi-indoor sampling sites (Paba et al, 2013). Table 3 shows the levels for each evaluated risk factor as maximum and mean observed values; moreover, the last column reported is a reference guideline for human health suggested in the literature both for occupational and life environments.…”
Section: Meanmentioning
confidence: 98%
“…The samples were then centrifuged at 5000 rpm for 10 min to remove the glass fibre, and the supernatant was collected in clean tubes. The suggested standard procedure for storage and determination was performed subsequently (Duquenne et al, 2013;Paba et al, 2013). The resulting clear supernatant was assayed for endotoxin evaluation.…”
Section: Gravimetric and Endotoxin Analysesmentioning
confidence: 99%
“…Endotoxins are a cell-wall component of gram-negative bacteria, and can be inhaled by workers [16,17]. It is suggested that they are involved in the development of respiratory disorders such as obstructive lung disease [17].…”
Section: Introductionmentioning
confidence: 99%